Estimating settlements due to tunnel boring machine excavation. Issue 3 (22nd June 2022) - Rattia, Victor; Divall, Sam; Gitirana, Gilson F. N.; Assis, Andre P.
Abstract : Soft-ground tunnel boring machines (TBMs) are the preferred solution for the construction of long tunnels and linear infrastructure assets, especially in urban areas. TBMs allow the control of tunnel-face stability, minimising the effects on surrounding ground. Unfortunately, existing methods for the assessment of ground surface movements due to TBM tunnelling either utilise complex and computationally expensive numerical analyses or rely on simplistic volume-loss theories, which do not consider the characteristics of the ground and TBM operation. This paper presents a simple formulation to estimate the immediate surface settlement due to the applied TBM support pressure, based on an analogy with the hyperbolic behaviour of stress–strain curves of soils. The variables chosen to describe the ground movement were the maximum surface settlement and volume loss, while the TBM face support pressure is used to describe the tunnel internal support pressure. Uncertainties due to the inherent variability of geotechnical parameters were also considered, resulting in the definition of lower and upper boundaries. Data from a series of centrifuge test results, with and without tunnel-face reinforcement by forepoles, and a real-scale TBM case study were used to validate the proposed model. The analyses show that the proposed model adequately represented the observed settlement data.